Knowledge and reported use of sport science by elite New Zealand Olympic class sailors - Legg, S. J.; Smith, P.; Slyfield, D.; Miller, A. B.; Wilcox, H.; Gilberd, C. (The Journal of Sports Medicine and Physical Fitness, 1997)
OBJECTIVE: This study enquired about the knowledge and reported use of sport science in elite Olympic class sailors. EXPERIMENTAL DESIGN: The sailors responded to a simple questionnaire. SETTING: The questionnaire was administered as part of an introductory seminar on sport science during a training camp. PARTICIPANTS: The participants were 28 (22 male, 6 female) elite New Zealand Olympic class sailors. INTERVENTIONS: None. MEASURES: The questionnaire asked whether or not they used a training race diary, enquired about their current and past injuries and their knowledge and use of sport science in the areas of nutrition, psychology and physical training. RESULTS: Only ten (36%) of the sailors kept a training/race diary. Whilst only four (14%) had a current injury, sixteen (57%) reported an injury in the previous three years. The injuries were in the lower back (45%), knee (22%), shoulder (18%), and arm (15%). Although nineteen (68%) of the sailors had experienced dehydration during racing, the average volume of fluid reported to be taken on a four hour sail was only 0.9 litre, of which only an average of 0.7 litres (77%) was reported to be drunk. All the sailors reported being sometimes (46%) to very often (3%) anxious before races and sometimes (43%) to always (7%) being frustrated with their own mistakes. Only one sailor reported never having negative thoughts whilst fifteen (53%) reported having them sometimes, and seven (25%) often or very often. Twenty-four (86%) of the sailors reported that they sometimes had a loss of concentration near the end of the race. Whilst eighteen (64%) reported practising relaxation and seventeen (61%) reported practising visualisation as a mental skill, only five (18%) practised progressive mental relaxation, two (7%) practised meditation and none practised yoga. Seventeen (61%) undertook strength/circuit training, ten (36%) flexibility and twenty-one (75%) off water aerobic training. Twenty-four (86%) reported undertaking on-water aerobic training. CONCLUSIONS: The results indicate that there is considerable scope for improvement in the knowledge and use of sports science amongst elite New Zealand Olympic class sailors.